Memory representation of aversive social experiences in Social Anxiety Disorder. (March 2023) - Seinsche, Rosa J.; Fricke, Susanne; Neudert, Marie K.; Zehtner, Raphaela I.; Walter, Bertram; Stark, Rudolf; Hermann, Andrea
Abstract: Aversive social experiences are proposed to be a risk factor for developing Social Anxiety Disorder (SAD). Many patients with SAD report associated daily life symptoms, such as intrusive re-experiencing (e.g., negatively distorted images of oneself), avoidance, alterations in cognitions and mood, as well as hyperarousal, resembling symptom dimensions of Posttraumatic Stress Disorder (PTSD). These PTSD-like symptoms may result from maladaptive processing and representation of the aversive social experiences in memory. Emotional hyperreactivity during memory retrieval of aversive social experiences is another feature of SAD which was found in previous studies. This study aimed to further investigate PTSD-like symptoms and emotional reactivity associated with etiologically relevant aversive social experiences and shed more light on a potential relationship between both. Eighty-five patients with SAD and 85 healthy controls (HC) participated in this cross-sectional study. It comprised an imagination task with self-report and physiological measures to assess emotional reactivity during the cued recall of the aversive social experience and clinical interviews to assess PTSD-like symptoms. We expected increased emotional reactivity and more severe PTSD-like symptoms in response to the aversive social experience in patients with SAD compared to HC, as well as a positive correlation between emotional reactivity and PTSD-like symptoms in patients with SAD. Indeed, patients with SAD showed emotional hyperreactivity (self-report, physiology) during the cued recall of the aversive social experiences, also when compared to two control memory conditions (neutral, negative non-social) and HC. Patients with SAD furthermore reported more severe PTSD-like symptoms compared to HC and intrusive re-experiencing symptoms were positively correlated with distress during imagery of the social aversive event in patients with SAD. These results might point toward a maladaptive representation of aversive social experiences in memory. Similar to PTSD, this maladaptive memory representation might promote the development of PTSD-like symptoms such as intrusive re-experiencing (e.g., in the form of intrusive self-images in patients with SAD), which might finally lead to and maintain symptoms of SAD. Highlights: Patients with Social Anxiety Disorder report the experience of etiologically relevant aversive social events. Physiological and subjective responses to memories of these events were assessed. These memories are associated with emotional hyperreactivity and symptoms similar to those of patients with Posttraumatic Stress Disorder Maladaptive representation of these events in memory might promote and maintain symptoms of Social Anxiety Disorder.